Pengembangan Modul Ajar Konten Proporsi Berbasis PBL untuk Memfasilitasi Kemampuan Pemecahan Masalah Matematis Siswa Fase D - Indra, Afifah Reghina; Saragih, Sehatta; Sakur, Sakur (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study aimed to develop a mathematics instructional module based on Problem-Based Learning (PBL) on proportion content to facilitate the mathematical problem-solving skills (MPSS) of Phase D students. The research method employed was Research and Development (R&D) using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research instruments included an instructional module validation sheet and response questionnaires for teachers and students. The validity of the module was evaluated in terms of face, content, and construct validity, while its practicality was assessed based on ease of use, material presentation, and visual appearance. Data were analyzed using quantitative and qualitative approaches. The results indicated that the developed instructional module met the criteria of very high validity, with an average validation score of 93.09, and was highly practical based on teacher and student responses, achieving a practicality score of 92.74. In conclusion, the PBL-based instructional module on proportion content is feasible for facilitating the mathematical problem-solving skills of Phase D students.